2010
DOI: 10.3324/haematol.2010.028365
|View full text |Cite
|
Sign up to set email alerts
|

The CEBPA gene is down-regulated in acute promyelocytic leukemia and its upstream promoter, but not the core promoter, is highly methylated

Abstract: ABSTRACTinformed consent under a protocol approved by the Medical School of Ribeirão Preto, University of São Paulo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
10
1
1
Order By: Relevance
“…The impact of CEBPA methylation on its expression remains controversial in AML samples. Fasan et al [24] observed a weak inverse correlation between decreased CEBPA level with CEBPA methylation in cytogenetically normal patients, whereas Santana-Lemos et al [21] did not find this association in acute promyelocytic leukemia. In this study, we disclosed the lower level of CEBPA transcript in patients with high methylation in spite of the statistically insignificant difference possibly due to the small number of patients analyzed.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The impact of CEBPA methylation on its expression remains controversial in AML samples. Fasan et al [24] observed a weak inverse correlation between decreased CEBPA level with CEBPA methylation in cytogenetically normal patients, whereas Santana-Lemos et al [21] did not find this association in acute promyelocytic leukemia. In this study, we disclosed the lower level of CEBPA transcript in patients with high methylation in spite of the statistically insignificant difference possibly due to the small number of patients analyzed.…”
Section: Discussionmentioning
confidence: 97%
“…CEBPA down-regulation has been identified in AML especially in patients with t(8;21) [21,31,32]. The impact of CEBPA methylation on its expression remains controversial in AML samples.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…16 Further, the more relaxed DNA binding conformation of the homodimerized fusion protein allows targeting of an extended number of sites, 17 potentially contributing to gene deregulation at numerous sites in the genome. In leukemic cells, repression of two important regulators of myeloid cell development, C/EBPA and PU.1 has been described, [18][19][20] including repression of PU.1 targets, 21 effects which have been suggested to contribute to leukemogenesis. However, the transcriptional repression model of PML/RARA was built mostly on studies of fully transformed cells and cell lines, making it difficult to distinguish the contribution of PML/RARA from that of secondary events.…”
Section: Introductionmentioning
confidence: 99%
“…Outras alterações moleculares, tais como em C/EBPα e em MYC concomitantes a ocorrência de PML-RARα, já foram demonstradas na LPA e associadas a leucemogênese desse tipo de leucemia (Santana-Lemos et al, 2011;Jones et al, 2010).…”
Section: Leucemiaunclassified